Characterisation of a cell-free supernatant obtained from cultures of Enterococcus faecalis DBFIQ E24 with antagonistic activity against bacteria, yeasts and moulds - Cardoso, Maria de Las Mercedes (2012)
Enterococcus faecalis DBFIQ E24 strain produces antimicrobial substances that inhibit the growth of food-borne pathogenic bacteria, yeasts and moulds. This broad antimicrobial spectrum was determined by obtaining the cell-free supernatant (CFS) and employing the agar-well-diffusion method. Its antibacterial activity was completely inactivated by the action of proteinase K and not affected by catalase action. Besides, it was stable to thermal treatments, showing maximum antibacterial activity at pH 7.0. Moreover, CFS showed a bactericidal effect against Escherichia coli DBFIQ Ec9 strain. All these interesting physicochemical properties allow that either CFS or E. faecalis DBFIQ E24 strain to be considered as potential food biopreservatives.